Problems of Improving Natural Resort Areas - Alloberdiyeva Durdona Uktamjon kizi (Scientific Trends, 2025)
The great attention of the world community to the problems of competition at various levels of the market space is explained by its natural regulatory role in the modern economy. The central idea in the competitive environment for any business entity is to achieve and maintain a competitive position for a long time. It is precisely in the transition to the information society, in the conditions of integration and globalization that competitiveness becomes the main category of market relations, contributing to the development of the economic environment. The nature of this development is the process of creating and constantly updating, actively implementing innovations based on effective management decisions. This article analyzes scientific theoretical considerations on the need to improve and develop the "resort area".
Keywords: Resort area, natural area, protection, recreation area, treatment, mineral, favourable climate.